1990
DOI: 10.1515/zna-1990-0813
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Vibrations, MIR and FIR Optical Properties of Boron and Icosahedral Boron-Rich Borides II. β-Rhombohedral Structure Group

Abstract: The lattice vibrations of the ß-rhombohedral boron structure group are investigated in detail by group theory. IR spectra of pure ß-rhombohedral boron as well as of B: Mn, B: Fe, B: Cu, and B: Cu/Al are presented and discussed. In comparison with boron carbide most of the absorption bands can be associated with certain vibrations. The vibration frequencies are determined by application of the phenomenological theory of Waser and Pauling, which thus yields a reliable estimation of the restoring forces ion these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 30 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…The lowest E u mode is mainly due to the bending motion of the linear chain, when f cc a is very small. In the case of a linear chain molecule XY 2 , the bending motion could have a high frequency above 400 cm −1 , as pointed out by Werheit et al [13]. This would be correct only if the chain were isolated from the surroundings.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The lowest E u mode is mainly due to the bending motion of the linear chain, when f cc a is very small. In the case of a linear chain molecule XY 2 , the bending motion could have a high frequency above 400 cm −1 , as pointed out by Werheit et al [13]. This would be correct only if the chain were isolated from the surroundings.…”
Section: Discussionmentioning
confidence: 90%
“…(ii) The highest band at 1560 cm −1 , which appears both in IR and Raman spectra, has been a controversial issue for a long time, as to whether it is a true phonon band of the crystal [10][11][12][13][14][15][16][17]. It was reported that the band disappeared from the Raman spectra when good-quality specimens were used [15].…”
Section: Introductionmentioning
confidence: 99%
“…They are bonded either directly by largely covalent intericosahedral B-B bonds or indirectly via single boron or foreign atoms, thus determining the different structural families ranging from α-rhombohedral boron with 12 atoms per unit cell to YB 66 with more than 1600 atoms per unit cell. Doping is possible by substitution or by accommodation of foreign atoms in specific interstitial sites [1][2][3][4][5]. Moreover the electronic properties can be modified by changing the chemical composition within sometimes large homogeneity ranges for specific compounds.…”
Section: Introductionmentioning
confidence: 99%